A systematic review on the applications of resting-state fMRI in Parkinson's disease: Does dopamine replacement therapy play a role?. (December 2015) - Tahmasian, Masoud; Bettray, Lisa M.; van Eimeren, Thilo; Drzezga, Alexander; Timmermann, Lars; Eickhoff, Claudia R.; Eickhoff, Simon B.; Eggers, Carsten
Abstract: Functional neuroimaging techniques provide important insight into the pathophysiology of neurodegenerative disorders such as Parkinson's disease (PD) in-vivo. Recently, resting-state functional magnetic resonance imaging (rs-fMRI) has been applied as a non-invasive tool in many studies to assess functional abnormalities observed in PD without the effects of particular motor or cognitive tasks. In this review, we summarized 50 original PD rs-fMRI studies and subdivided them based on the medication status of the patients to highlight the impact of dopamine replacement therapy (DRT) when rs-fMRI was used to assess patients with PD. Although there are many different published approaches to analyzing rs-fMRI in PD, it seems that DRT plays a critical role in the functional reorganization of the brain throughout all of these approaches. In particular, studies that compared PD patients with and without medication demonstrated that DRT normalizes aberrant functional patterns in PD and leads to an improvement of PD symptoms. Thus, researchers should consider DRT as a confounding factor, which could result in misinterpretations. We suggest that performing rs-fMRI in de novo patients could be a method of choice to study the fundamental functional abnormalities in PD independent of the effects of DRT. However, it is necessary to carefully control for excessive involuntary head motions in the patients not receiving DRT. On the other hand, recruiting patients under daily DRT might be favorable to assess particular interventions in clinical routine.